Pitolisant, a wake‐promoting agent devoid of psychostimulant properties: Preclinical comparison with amphetamine, modafinil, and solriamfetol. Issue 5 (23rd August 2021) - Krief, Stéphane; Berrebi‐Bertrand, Isabelle; Nagmar, Isabelle; Giret, Martin; Belliard, Simon; Perrin, David; Uguen, Marilyne; Robert, Philippe; Lecomte, Jeanne‐Marie; Schwartz, Jean‐Charles; Finance, Olivier; Ligneau, Xavier
Abstract: Several therapeutic options are currently available to treat excessive daytime sleepiness (EDS) in patients suffering from narcolepsy or obstructive sleep apnea. However, there are no comparisons between the various wake‐promoting agents in terms of mechanism of action, efficacy, or safety. The goal of this study was to compare amphetamine, modafinil, solriamfetol, and pitolisant at their known primary pharmacological targets, histamine H3 receptors (H3R), dopamine, norepinephrine, and serotonin transporters, and in various in vivo preclinical models in relation to neurochemistry, locomotion, behavioral sensitization, and food intake. Results confirmed that the primary pharmacological effect of amphetamine, modafinil, and solriamfetol was to increase central dopamine neurotransmission, in part by inhibiting its transporter. Furthermore, solriamfetol increased levels of extracellular dopamine in the nucleus accumbens, and decreased the 3, 4‐dihydroxyphenyl acetic acid (DOPAC)/DA ratio in the striatum, as reported for modafinil and amphetamine. All these compounds produced hyperlocomotion, behavioral sensitization, and hypophagia, which are common features of psychostimulants and of compounds with abuse potential. In contrast, pitolisant, a selective and potent H3R antagonist/inverse agonist that promotes wakefulness, had no effect on striatal dopamine, locomotion, or food intake. In addition, pitolisant, devoid of behavioral sensitization by itself, attenuated the hyperlocomotion induced by either modafinil or solriamfetol. Therefore, pitolisant presents biochemical, neurochemical, and behavioral profiles different from those of amphetamine and other psychostimulants such as modafinil or solriamfetol. In conclusion, pitolisant is a differentiated therapeutic option, when compared with psychostimulants, for the treatment of EDS, as this agent does not show any amphetamine‐like properties within in vivo preclinical models. Abstract : The wake‐promoting agents amphetamine, modafinil, solriamfetol and pitolisant were compared. The first three drugs cause dopamine release in the striatum, hyperlocomotion, behavioral sensitization and hypophagia, common features of psychostimulants, in contrast to pitolisant.